Q. 164.3( 3 Votes )

[(–8) × (–3)] × (–4) is not equal to
A. (–8) × [(–3) × (–4)]

B. [(–8) × (–4)] × (–3)

C. [(–3) × (–8)] × (–4)

D. (–8) × (–3) – (–8) × (–4)

Answer :

[(-8) × (-3)] × (-4) = -96


Option A is incorrect as


As (-8) × [(-3) × (-4)] = -96 is equal to [(-8) × (-3)] × (-4)


Option B is incorrect as


As [(-8) × (-4)] × (-3) = -96 is equal to [(-8) × (-3)] × (-4)


Option C is incorrect as


As [(-3) × (-8)]× (-4) = -96 is equal to [(-8) × (-3)] × (-4)


Option D is the correct option since, [(-8) × (-3)] × (-4) is not equal to (-8) × (-3)-(-8)× (-4) = 24-32 = -8

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.